2010/11 McMurdo Station Snow Road Strength and Maintenance - Melendy,Terry D; Shoop,Sally (2017)
During the 2010/11 Antarctic field season, the Cold Regions Research and Engineering Laboratory (CRREL) conducted a snow roads and transportation study for a second year at McMurdo Station. Part of this study included tracking the road maintenance and temperature and testing the road strength at predetermined mile markers along the 13 miles of snow roads located on a permanent ice shelf that connects the (now closed) Pegasus Airfield to McMurdo Station. These data were recorded for each lane of road at six locations over 5 months. A Clegg Impact Hammer and a Rammsonde snow cone penetrometer were used to capture both the surface strength and the strength of the road with regard to depth. The team collected temperature data by using a temperature probe inserted into the snow to measure temperature of the air, snow surface, 7.6 cm down from surface, and 15.2 cm down from surface.